Comparison of the Environmental, Social, and Governance Stock Index with Sharia Stock Index Performance Before and During the COVID-19 Pandemic in Southeast Asia - Een Nuraeni; Faaza Fakhrunnas (International Journal of Islamic Economics and Finance (IJIEF), 2022)
COVID-19 is a pandemic event with a global impact from a health and economic point of view. The number of confirmed cases of COVID-19 that continues to grow has caused several countries to implement lockdown policies. However, it has implications for an increasingly depressed stock market. Thus, it can affect the performance of stock indexes in various countries. For this reason, this research aims to examine the effects of the COVID-19 pandemic on the Islamic stock index and the environmental, social, and governance stock index in Southeast Asia and then compare the two indexes when responding to the COVID-19 pandemic. The models used in this research were event study and Vector Error Correction Model (VECM). This study utilized time-series data with a five-month daily period from December 2019 to April 2020. The event study model results showed that the number of positive cases of COVID-19 significantly affected the stock index performance, except for the ESG stock indexes in Singapore. Moreover, the VECM results revealed that the number of positive cases of COVID-19 had a significant effect on the stock index performance in the long and short term, except for the sharia stock index, which did not have a significant impact on the short term in Singapore and did not have a significant impact on the long term in Malaysia, namely the HIJRAH index.